2021
DOI: 10.1091/mbc.e20-08-0508
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect regulation of Pom1 cell size pathway by the protein phosphatase 2C Ptc1

Abstract: The fission yeast cells Schizosaccharomyces pombe divide at constant cell size regulated by environmental stimuli. An important pathway of cell size control involves the membrane-associated DYRK-family kinase Pom1, which forms decreasing concentration gradients from cell poles and inhibits mitotic inducers at mid-cell. Here, we identify the phosphatase 2C Ptc1 as negative regulator of Pom1. Ptc1 localizes to cell poles in a manner dependent on polarity and cell-wall integrity factors. We show that Ptc1 directl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…They found that Pom1p travels between clusters in a “hopping” manner to move from the cell tip toward the medial region of the cell, with these clusters creating the gradient. Additionally, they confirmed Pom1p distribution at the plasma membrane through the cycle of Pom1p gradient phosphorylation and de-phosphorylation events [ 49 ]. revealed that the PP2C phosphatase Ptc1p dephosphorylates Pom1p in vitro , and both proteins are able to form complexes in vivo .…”
Section: Mid1p-dependent Assembly Of Acr In S Pombe ...mentioning
confidence: 62%
“…They found that Pom1p travels between clusters in a “hopping” manner to move from the cell tip toward the medial region of the cell, with these clusters creating the gradient. Additionally, they confirmed Pom1p distribution at the plasma membrane through the cycle of Pom1p gradient phosphorylation and de-phosphorylation events [ 49 ]. revealed that the PP2C phosphatase Ptc1p dephosphorylates Pom1p in vitro , and both proteins are able to form complexes in vivo .…”
Section: Mid1p-dependent Assembly Of Acr In S Pombe ...mentioning
confidence: 62%
“…In the study of cell size dynamics, a core issue is to understand the size homeostasis strategies in various cell types, especially in fission yeast [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. There are three popular phenomenological models of cell size control leading to size homeostasis [52]: (i) the timer strategy which implies a constant time between successive divisions regardless of initial size; (ii) the sizer strategy which implies cell division upon attainment of a critical size, and (iii) the adder strategy which implies a constant size addition between consecutive generations.…”
Section: Introductionmentioning
confidence: 99%
“…Fission yeast has been an attractive model organism for several decades in studies of eukaryotic cellular growth [1][2][3][4][5][6][7]. Revealing the rules of cellular growth is crucial in understanding how size control mechanisms maintain size homeostasis in steady-state cell cultures, and this point has also been extensively studied in fission yeast [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%